Bayesian Networks: With Examples in R. By M.Scutari and J.‐B.DenisBoca Raton, FloridaCRC Press. 2014. 241 pages. UK £69.99 (hardback). ISBN 978‐1‐48222‐558‐7. (15th December 2017) - Vignes, Matthieu; Sammarro, Mélodie; Schrefheere, Anthime; White, Alex; Marsland, Stephen
Abstract : Bayesian networks are now pedagogically factorised in R with tremendous applications by Mario Scutari and Jean‐Baptiste Denis' book.